A Comparative Study Of Ppv Analysis Of Tunnel Rounds Using Both Non Electric And Programmable Electronic Detonation - Andrew Wetherelt (International Society of Explosives Engineers, 2007)
Blast vibrations are of paramount importance in a society where ever increasing development is putting more stringent requirements on their control. Increasing civil development and more complex extraction scenarios make the trade off between proficient vibration control and productivity difficult to ascertain. Historically, reduction of induced vibrations levels was achieved through a reduction of MIC’s leading to smaller but more frequent blasts in order to meet extraction targets.